Penser la pluralité des monnaies à partir de Polanyi : un essai de typologie - Blanc, Jérôme (ERES, 2014)
A large number of currencies has emerged for thirty years, far beyond the national currencies alone. It includes systems created by groups of citizens, others by territorial communities, and others by private companies for their own benefit. These currencies take various forms, ranging from electronic money on smart cards to settlement systems ...
Keywords: currencies; modern currencies

Maintenir l'ordre économique, Maintaining the economic order - Gayon, Vincent; Lemoine, Benjamin (Politix, 2014)
La sociologie des politiques économiques défendue dans cet article prend pour objet le travail permanent de construction, de naturalisation et de maintien de l’ordre économique déployé par une multitude d’acteurs et d’instruments techniques. Il s’agit d’ouvrir des enquêtes sur la façon dont prennent forme les processus de désencastrement et de réencastrement de l’économie vis-à-vis des institutions politiques et sociales. Cette piste est suivie en quatre temps. D’abord en soulignant la portée sociogénétique de l’œuvre de Karl Polanyi et son insistance sur l’émancipation disputée et incertaine des pratiques de production et d’échange à l’égard des tutelles traditionnelles. Puis en montrant comment l’invention de l’économie en tant que sphère d’activité autonome suscite foule de résistances et de « mondes économiques renversés », opposant leurs propres normes aux « lois » supposées de l’économie. La configuration de l’après Seconde Guerre mondiale est revisitée comme un laboratoire exemplaire de réencastrement politico-étatique de l’économie. Le désencastrement néolibéral des marchés financiers à l’échelle internationale recompose ensuite les comptes de la puissance publique et privée. Ces ordres économiques balisent simultanément des zones d’accès et, réciproquement, de non-droit à la discussion publique et politique., ENG: The sociology of economic policies argued in this article investigates the permanent work of construction, naturalization and maintenance of the economic order made by a multitude of actors and technical instruments. It consists in describing how the doctrinal project of economy disembeddedness takes shape, detaching itself from the political and social institutions. This program is developed through four steps. First, by offering a constructivist reading of Karl Polanyi writings and highlighting the author’s insistence on the uncertain and contested process of production and exchanges’ practices emancipation vis-à-vis traditional guardianship. Then, by showing how the invention of the economy as an autonomous sphere of activity raises crowd resistance and « reversed economic worlds » settling their own standards and laws by opposition to the economy « rules » and values. The after World War Two configuration is revisited as an exemplary laboratory of Politics and State re-embeddedness of the economy. Then, neoliberal disembeddedness of global capital markets reshapes accounts of public and private powers. These economic orders simultaneously mark out areas of access to and, conversely, of non-entitlement to public and political discussion.
Keywords: constructivist; embeddedness

Cartographie des échanges - Steiner, Philippe (Nouvelles Perspectives en Sciences Sociales, 2014)
In this article, I examine the main typologies of transaction that have been built from Auguste Comte to Karl Polanyi, Marcel Mauss, and Philippe Descola. Then, I suggest to reconsidering Polanyi's typology, the most common in contemporary economic sociology, and to limit the time span to modern societies. Accordingly, it is possible to map seven forms of transaction and the related institutions at work in our societies. In conclusion, the political consequences of the existence of these different forms of transaction are highlighted. (English)
Keywords: don; exchange; gift; héritage; inheritance; marché; market; solidarity; solidarité; échange

Le don fondateur du lien social, le cas de l'économie de marché - Lasida, Elena (Transversalités, 2014)
Le don et l’échange marchand sont généralement opposés. Pourtant, l’un et l’autre apparaissent comme fondateurs du lien social dans la mesure où l’on prend en compte la relation qu’ils créent au niveau interindividuel et collectif. Le don apparaît ainsi associé à une certaine forme de réciprocité et le marché à une certaine forme de gratuité., Gift and commodity exchange are generally opposed. But both appear as founders of the social bond when we consider the relationship they create between people and in society. The gift is thus associated with some form of reciprocity and the market with some form of gratuitousness.
Keywords: don; lien social; marché; relation; réciprocité; valeur; économie; économie sociale et solidaire